BURROWING CENTRAL AMERICAN MANGROVE LAND CRABS AND THEIR BURROW ASSOCIATES - Bright, Donald B. (Marine Research in Indonesia, 1977)
General remarks on the following aspects of the life history of land crabs are presented: migration, shedding of eggs, molting, juveniles and food. The nature of the crab burrows and the associated burrowdwelling organisms also are presented. The distribution of burrowing land crabs is discussed with respect to three general plant formations in gecarcinid crab localities, ie., Mangrove-Estero, Island and Strand patterns.